IoT-based Remote Control Water Distribution System - Chavhan, Sushilkumar; Gawande, U. H.; Bhoyar, Dinesh; Rangari, Sudhir; Gardi, Manish; Gaikwad, Anil (International Journal of Intelligent Systems and Applications in Engineering, 2023)
This paper presents the design and implementation of an IoT-based remote control water distribution system. The system allows the water supply operators to control valves remotely to regulate the flow of water. The valve control is done using an IoT platform, which allows the system to be controlled remotely through a mobile application. Operators can use a mobile application to quickly respond to leakage events and close valves before significant damage occurs. In addition, the DTMF calling system can be used to remotely send numeric information or signals using the touch-tone keypad on their phone to close the valve even in the absence of an internet connection. The system is designed to improve the efficiency of water distribution by reducing water loss and providing accurate control over the distribution of water. The prototype was tested, and the results showed that it was able to provide accurate control over the distribution of water and reduce water loss. The system is scalable and can be adapted to different water distribution systems. Overall, the IoT-based remote control valve system presents a promising solution for improving the efficiency and sustainability of water distribution systems.